Gestão ambiental: perfil profissional e formação em cursos superiores de tecnologia e de bacharelado - Schenkel, Cladecir Alberto (2012)
The focus of this research was to study the professional profile of graduates from higher education courses in Environmental Management and of professional courses of Bachelor and Technology. This research is due the following reasons: courses are a little over ten years of existence, are in the process of building an identity, are new to the institutions that offer and also require a new look at the curriculum and academic knowledge. The objective was to investigate the professional profile of the Environmental Manager and curriculum adopted for its formation. The working hypothesis was that, to address the complexity of this professional training, the teaching model and curriculum needs to break with the dominant model in the Brazilian higher education. Guided by the paradigm of complexity, has become the choice of qualitative research, therefore, the data of interest to disclose the matter of the proposed research are made up of meanings, readings, prints, among others, as sources with bibliographies, documents and people. We selected four institutions offering the course Environmental Management, two courses of Bachelor and two of Technology with different curricular approaches: Escola Superior de Agricultura Luiz de Queiroz - ESALQ, Universidade de São Paulo (Bachelor disciplinary), Universidade Federal do Paraná - UFPR Campus Litoral (Bachelor modular interdisciplinary), Centro Federal de Educação Tecnológica Celso Suckow da Fonseca, CEFET/RJ (Technology disciplinary), Instituto Federal do Triângulo Mineiro - IFTM Campus Uberaba (Technology modular). The literature review sought to raise questions about the epistemological and philosophical Modern Science, knowledge, education and curriculum, based on contributions from Morin, Santos, Adorno and Horkheimer, Leff, Apple, Sacristan, Goodson, among others. For the documentary research projects were selected pedagogical courses (curriculum) Environmental Management and other relevant documents. The field research was carried out using the technique of semistructured interviews with the course coordinators, teachers, students and graduates of four courses in Environmental Management, whose sample was characterized as intentional (stratified and directed). Analysis of data was performed using the technique of content analysis to identify, interpret and contextualize the ideas contained in documents and speeches of the interviewees. The results confirmed the hypothesis of the research, because the traditional disciplinary curriculum, the courses of Bachelor of ESALQ and of Technology of CEFET/RJ showed greater degree of limitation for the formation of the Environmental Manager in relation to modular curriculum (IFTM Uberaba and UFPR Litoral), especially with regard to the formation of an integrated look (systemic view) of environmental issues. On the other hand, the course of Bachelor of Environmental Management UFPR Litoral, with a modular curriculum and interdisciplinary pedagogical practice oriented by project pedagogy, presented the results consistent with the formation of a trader. The course of Technology IFTM Uberaba presented limitations due to the lack of identity of the course (Blending Management and Environmental Sanitation) and a design module as simple grouping of related disciplines.